2018
DOI: 10.1098/rspb.2018.1710
|View full text |Cite
|
Sign up to set email alerts
|

Rearing a virulent common cuckoo is not extra costly for its only cavity-nesting host

Abstract: Virulent brood parasites refrain from arduous parental care, often kill host progeny and inflict rearing costs upon their hosts. Quantifying the magnitude of such costs across the whole period of care (from incubation through to parasite fledgling independence) is essential for understanding the selection pressures on hosts to evolve antiparasitic defences. Despite the central importance of such costs for our understanding of coevolutionary dynamics, they have not yet been comprehensively quantified in any hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 46 publications
(114 reference statements)
3
26
0
1
Order By: Relevance
“…It is logical and reasonable that for iteroparous hosts, those that suffer higher costs of rearing a parasite gains less fitness than those that suffer the lower cost of rearing parasites. However, the key conclusion of Samaš et al [4] was that rearing the parasite per se was not associated with overall higher costs to hosts above the natural levels imposed by efforts to rear their own progeny, and this in part explains the low levels of known host counter-defences in hosts. The problem here is that Samaš et al [4] compared the costs of rearing the parasite with that of rearing the host's own progeny rather than comparing the higher cost of rearing a parasite with the lower cost of rearing a parasite.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is logical and reasonable that for iteroparous hosts, those that suffer higher costs of rearing a parasite gains less fitness than those that suffer the lower cost of rearing parasites. However, the key conclusion of Samaš et al [4] was that rearing the parasite per se was not associated with overall higher costs to hosts above the natural levels imposed by efforts to rear their own progeny, and this in part explains the low levels of known host counter-defences in hosts. The problem here is that Samaš et al [4] compared the costs of rearing the parasite with that of rearing the host's own progeny rather than comparing the higher cost of rearing a parasite with the lower cost of rearing a parasite.…”
mentioning
confidence: 99%
“…the nestling stage), whereas the costs of the fledgling stage are so far not quantified [4]. Recently, Samaš et al [4] for the first time measured and quantified the immediate costs of rearing a cuckoo (Cuculus canorus) chick across all developmental stages of its redstart (Phoenicurus phoenicurus) host [4]. Contrary to traditional assumptions, they found that raising a cuckoo chick per se was not associated with overall higher costs to hosts above the natural levels of cost of raising their own chicks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in the case of parasites whose nestlings are reared alone in host nests, several studies have found that host provisioning rates were either similar between parasitized and non-parasitized broods (Brooke and Davies 1989, Kilner et al 1999, Mark and Rubenstein 2013, Samaš et al 2019, this study), or were lower in parasitized nests. For example, common cuckoo nestlings reared by rufous bush robins Cercotrichas galactotes received less food than a normal host brood (Martín-Gálvez et al 2005), or were fed less frequently when they are reared by common redstarts Phoenicurus phoenicurus (Samaš et al 2018).…”
Section: Nest Provisioning Rate and Parasitismmentioning
confidence: 99%
“…Brood parasitism might also influence host parental care (Krüger ). For instance, studies on brood parasite–host systems where parasitic and host nestlings do not share the nest have either failed to find statistically significant differences in provisioning rate between parasitized and non‐parasitized nests (Kilner et al , Mark and Rubenstein , Samaš et al ), or found lower provisioning rates in parasitized nests (Soler et al , Požgayová et al , Samaš et al ). In contrast, studies on brood parasite–host systems in which parasitic and host nestlings share the nest (e.g.…”
Section: Introductionmentioning
confidence: 99%